2015
DOI: 10.1016/j.aqrep.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal infection due to Kudoa sp. (Myxozoa) in mapara catfish, Hypophthalmus marginatus

Abstract: a b s t r a c tThe present study describes lesions caused by Kudoa sp. in the esophageal tissue of mapará catfishes (Hypophthalmus marginatus) collected from Cametá, Tocantins River in the northern Brazil. Fifty refrigerated H. marginatus specimens were dissected and tissue samples were for embedded in paraffin and stained with hematoxylin-eosi, Masson's trichrome and Giemsa. Pseudocysts of whitish color were observed in the esophagus region. The parasites had four valves and other morphological characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The myxozoan genus Kudoa presents tropism towards the skeletal musculature, and is known to be responsible for postmortem myoliquefaction in the host (Kristmundsson and Freeman 2014), although these parasites have also been described in other types of tissue and organs, such as the intestine (Yurakhno et al 2007), ovary (Mansour et al 2015, oesophagus (Velasco et al 2015b), and heart (Abdel-Ghaffar et al 2016). The spores of this genus may be star-shaped, square or rounded quadrangular (Casal 2009), and are generally made up of four or more shell valves and polar capsules of equal number (Whipps et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The myxozoan genus Kudoa presents tropism towards the skeletal musculature, and is known to be responsible for postmortem myoliquefaction in the host (Kristmundsson and Freeman 2014), although these parasites have also been described in other types of tissue and organs, such as the intestine (Yurakhno et al 2007), ovary (Mansour et al 2015, oesophagus (Velasco et al 2015b), and heart (Abdel-Ghaffar et al 2016). The spores of this genus may be star-shaped, square or rounded quadrangular (Casal 2009), and are generally made up of four or more shell valves and polar capsules of equal number (Whipps et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the Amazon region, mixosporean of the genus Kudoa have been found infecting the muscle of Aequidens plagionatus (Casal et al 2008), Chaetobranchopsis orbicularis (Azevedo et al 2016, Sindeaux Neto et al 2017 and Plagioscion squamosissimus (Oliveira et al 2015), while in Hypophthalmus marginatus, Velasco et al (2015b) found this parasite in the muscle layer of the intestine. In the present study, we describe a new species, Kudoa viseuensis n.…”
Section: Introductionmentioning
confidence: 99%